(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
This article analyzes the historical stages of studying the cultural heritage sites of the Surkhan Valley. It focuses on archaeological research conducted from the late 19th century to the 1980s, including early topographic observations during the Russian Empire, systematic excavations of the Soviet era, and the application of new technological approaches in the years of independence. The paper discusses the scientific study of major archaeological sites such as Ayrtam, Kara-Tepe, Fayaz-Tepe, and Dalverzin-Tepe, emphasizing their role in the formation of the Uzbek archaeological school and the international importance of the Surkhan Valley’s cultural heritage.